FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH TERHADAP PEMERINTAH DAERAH BERDASARKAN UNDANG-UNDANG DASAR 1945 - Zulfia, Sophi (Yustitia, 2024)
Function Local House of Representatives to local governments based on the 1945 Constitution, the main problem of this research is to find out how the implementation of the regulation of the DPRD's supervisory function on local governments in the Unitary State of the Republic of Indonesia which is based on decentralization, with identification studies. what indicators are used to optimize the local House of Representaitives oversight function of local governments and what is the proper concept of supervision that can be carried out by the Local House of Representatives on local governments.